Influence of extractive on the porosity of oil palm (Elaeis guineensis Jacq.) stem - A. Bakar, Balkis Fatomer (2014)
In this study, an investigation was conducted to determine the basic properties (moisture content and density) of the oil palm stem and amount of extractives content that can be extracted from the sample. Porosity studies were also conducted on the oil palm stem in different exposure conditions (dried and green) and the influence of extractive on the porosity was examined. Oil palm trees were selected randomly from the species Elaeis guineensis Jacq. from Taman Pertanian Universiti located in Universiti Putra Malaysia,Serdang, Malaysia. Each of the tree were cut along the tree height into three main parts namely bottom, middle and top. Each part was further cut into three sections labelled as outer, inner and centre across the transverse direction of oil palm stem. Technical Association of the Pulp and Paper Industry (TAPPI) standards were employed for water extractives (cold water and hot water) and also acetone extractives. The green moisture content of the oil palm stem was found higher at the middle with average of 221.8% and lowest was at bottom with 158.4%. Across the transverse direction, centre section always had higher moisture content regardless of the tree height and the lowest was found at outer section with average of 260.7% and 115.3%, accordingly. The density of oil palm stem was found inversed with moisture content as the highest density was found at bottom with average of 0.46 g/cm³ and the lowest was at middle with 0.37 g/cm³. Outer consistently gave higher density compared to centre section with 0.55 g/cm³ and 0.30 g/cm³. The coefficient of determination (R2) obtained between moisture content and density was high with 0.83. In non-sequential method, hot water extractives gave higher results compared to other solvents with average of 26.8% of total extracted compounds. Whereas in the sequential method, cold water was found higher with average of 21.3%. Comparing the methods, sequential extraction method gave greater amount of extractives as the samples had gone through three different solvents continuously. Whilst, parenchyma cells is proven to contribute three times higher of extractives content compared than vascular bundles. For theoretical porosity in dried and green condition, samples taken from centre section at middle part had highest average percentage of 79.4% and 78.2%, respectively and the least was found at outer section at bottom part with 71.7% and 69.0%, accordingly. Whereas, experimental porosity was found higher at centre section at top part for dried condition and at centre section of middle part along the oil palm tree height for green condition. Experimental porosity surpassed the theoretical porosity values as a result from the effects of condition exposure of the samples at the upper part of the oil palm tree (middle and top). However, there is no dependency of extractives content towards porosity found in this study. This study concluded that moisture content and density of oil palm stem was affected by the location (longitudinal and transverse direction) of the sample taken. Extractives content was found higher at sample which consist higher portion of parenchyma cells. Oil palm stem sample in green condition resulted higher experimental porosity compared to dried condition. Porosity of oil palm stem has low influence by its extractives content rather than its anatomical structure. The study suggests that oil palm stem can be treated by impregnation or preservation process in green condition.